STIGMA GURU BIMBINGAN KONSELING (Mengubah Mainset Peserta Didik Terhadap Guru Bimbingan Konseling Melalui Keterampilan Komunikasi Interpersonal) - Amalia Alvi; Mafufah Hastin (Jurusan Bimbingan dan Konseling, 2019)
The writing of this article aims to explain the importance of changing the mainset of students towards teachers guidance and counseling through interpersonal communication skills. Communication is very important for the continuity of counseling, because the quality of relationships can determine success in counseling. Interpersonal communication skills are indispenseble in counseling to make it easier to establish good relationships and can bridge studentss in problem solving all the obstacles and problems that are being faced and can eliminate the stigma that has been pinned on the BK teacher.